Puerperal Period Reproductive Disorde,rs in Surti Buffaloes During Different Parity - MURUGEPPA, A; DUBEY, B M (The Indian Journal of Animal Reproduction, 2023)
The overall incidence of various reproductive disorders during puerperal period were studiedin 622 calvings of 292 farm born surti buffaloesfro m the herd of All India Co-ordinated ResearchProject on Buffaloes, Main Research Station,Un iversity of Agricultural Sciences; Dharwad. Theoverall incidence of retention of placenta, septic metritis, metritis, endometritis, vaginitis, Pyometraand Post-partum cervicovaginal prolapse in 622 calvings were 7.56, 8.68, 9.81. 8.36, 1.77, 7.56 and 2.40 percent respectively. Thepercentage incidence of all the reproductive disorders were comparatively low in the first parityfollowed by increasing tendency during second,third and fourth parities.
Keywords: Puerperal Period; Surti Buffaloes; Reproductive Disorder